To solve problems that have the expression of the form 2(x + 90), you have to open the brackets. When that is done each term inside the bracket is multiplied by the term outside.
In the case of 2(x + 90), you would have to multiply both x as well as 90 by 2.
2(x + 90)
=> 2*x + 2*90
=> 2x + 180
Similarly if you have to deal with something like (a + b)(c + d)
=> a(c + d) + b(c + d)
=> ac + ad + bc + bd
The result of 2(x + 90) is 2x + 180
In order to solve the brackets in math, you can expand them.
In order to expand, you must multiply the component outside the bracket with what is inside the bracket.
For example, if there is 2(x+90), you can multiply 2 by x and 90.
so the answer would be 2x+180.
the bracket mean multiplication.
2(x+90) = 2x+180
when you get brackets like that you have to multiply it
for example 2(x+90)=2x+180